Customer-Centric Technology: A Science Mapping of Marketing Transformation - Zulfikar, Rizka; Suryadi, Nanang; Valen Prasarry, Yudhita (AMAR (Andalas Management Review), 2025)
This research aimed to analyze the impact of technology on marketing practices, from the adoption stage to the creation of customer experience, through a bibliometric approach. Using 133 articles published between 2000 and 2024 obtained from Scopus.com database, the study compiled a comprehensive literature analysis to identify key trends, dominant research themes, and gaps in the literature. The article selection process was carried out using the PRISMA method with keywords such as "technology adoption," "digital marketing," and "customer experience,". The bibliometric process was carried out using bibliometric analysis tools such as Biblioshiny-R. The results showed that technologies such as artificial intelligence (AI), big data analytics, and the Internet of Things (IoT) have a significant role in improving personalization and marketing efficiency, while creating a more immersive and satisfying customer experience. The study identified patterns of author networks, leading journals, as well as research trends that focus on the integration of technology in customer experience design. These findings make a theoretical contribution by strengthening the understanding of the relationship between technology adoption and customer experience, as well as practical implications for companies in developing technology-based marketing strategies.